Evaluation of Helicobacter pylori Stool Antigen Test Results According to Demographic and Clinical Characteristics of Patients - Mustafa Erdem Sarp; Serranur Altun Sarp; Mediha Uğur; Özkan Bahadir (Farabi Tıp Dergisi, 2026)
Objective: This study aimed to evaluate Helicobacter pylori (H. pylori) antigen test results in stool samples in relation to the epidemiological features of patients.Material and Methods: This retrospective study included patients who underwent H. pylori antigen testing between 2022 and 2024. Analyses were performed using the H. pylori antigen test kit produced by RDS Laboratory Systems (Ankara, Türkiye). Demographic and clinical data were obtained from the hospital information system. Positivity rates were evaluated according to demographic features, departments, and the date.Results: H. pylori antigen testing was performed on 2024 patients. The overall positivity rate was found to be 12% (n = 243). Among the H. pylori antigen-positive patients, 70.0% (n = 170) were female and 30.0% (n = 73) were male. Positivity was significantly higher in females (p = .023). When assessed by age groups, the highest positivity rate (13.6%, n=61) was observed in aged 60–69. Distribution of departments, 68.2% (n = 1381) from gastroenterology, 29.9% (n = 605) from internal medicine, and 1.9% (n = 38) from others. H. pylori antigen positivity was identified in 10.5% (n = 145) of the samples submitted from gastroenterology and in 15.2% (n = 92) of samples from internal medicine.Conclusion: In this three-year study, stool H. pylori antigen positivity was relatively low and was more frequent among female patients, with the highest positivity rate observed in the 60–69-year age group. Most test requests originated from gastroenterology and internal medicine departments. These findings provide regional data and suggest that stool antigen testing may support targeted diagnostic evaluation in clinically appropriate patients rather than population-based screening.